Circadian typology is related to emotion regulation, metacognitive beliefs and assertiveness in healthy adults - Antúnez-Vílchez, Juan Manuel (PLOS One, 2020)
This study explores the relationship between circadian typology and three key psychological constructs: emotion regulation, metacognitions, and assertiveness, considering possible sex differences. A total of 2,283 participants (833 women), aged 18-60, completed questionnaires assessing morningness-eveningness, emotion regulation, metacognitions, and assertiveness. The findings revealed significant effects of circadian typology on several psychological factors, including cognitive reappraisal, metacognitions, negative beliefs about uncontrollability and danger, cognitive confidence, cognitive self-consciousness, and assertiveness. Morning-type individuals scored lower on maladaptive metacognitive beliefs and higher on cognitive reappraisal and assertiveness compared to evening-type participants, with neither-type falling in between. The study suggests that evening-type individuals are more prone to maladaptive thinking patterns and may struggle with reappraisal of emotional situations and assertiveness. These findings highlight evening-type as a potential risk factor for psychological issues, while morning-type may serve as a protective factor. Further longitudinal research is needed to confirm these associations.
Keywords: Ritmos circadianos; Circadian typology; Emotion regulation; Metacognitions; Metacognitive; Assertiveness